Quantifiable Simulation of Quantum Computation beyond Stochastic Ensemble Computation (Adv. Quantum Technol. 2/2018). Issue 2 (23rd October 2018) - Bang, Jeongho; Ryu, Junghee; Lee, Chang‐Woo; Yee, Ki Hyuk; Lee, Jinhyoung; Son, Wonmin
Abstract : A model of quantum computation (QC) is compared with a generalized classical computation model, named stochastic ensemble computation (SEnC), in article number1800037 by Jeongho Bang, Jinhyoung Lee, Wonmin Son and co‐workers. SEnC runs in an ensemble consisting of finite copies of single probabilistic entities, and hence is a generalized probabilistic Turing machine. Impossibility of simulating a QC in the SEnC is proved, manifesting "QC is characterized beyond any classical probabilistic computation, " i.e., SEnC ⊆ QC.